Building an Anti-Corruption Village with Local Wisdom in Tourism Towards the Richest Village in Indonesia (A Closer Look at Kutuh-Badung-Bali Village) - Amalia Syauket; Ali Johardi Wirogioto; Donny Ramadhan (Sociological Jurisprudence Journal, 2023)
In the midst of the dark image of village funds due to the corruption of the village head, there is a lamp in the south of Bali. Kutuh Village, which was once poor and arid, has now become an independent village thanks to village funds from the government. Kutuh Village has received village funds of around IDR 3.5 billion. The village budget management sector was recorded as the largest contributor to state losses in 2018. The biggest challenge in managing Village Funds comes from the uniqueness of the village government system in Bali with the concept of dualism of power: official villages and traditional villages, in the development of culturally-inspired Balinese tourism. this study aims to capture how local wisdom in the field of tourism in Kutuh Village, especially as a means of mitigating fraud in managing village funds. This study uses normative and empirical juridical research. Opportunities for fraud are mitigated by implementing local wisdom which is still very much embedded in the daily life of the people of Kutuh Village, which is based on the principle: from by Krama and for karma (citizens), with the ultimate goal of strengthening traditional institutions and religious traditions with wisdom local in it in order to realize prosperity and harmony between elements in accordance with the philosophy of trihita karana and in essence this is the mandate of giving village funds.